PENGARUH LEVERAGE DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SUBSEKTOR TAMBANG LOGAM DAN MINERAL LAINNYA YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Lamhot Beriman Simbolon; Remista Simbolon (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This research was conducted to find of leverage and audit committee in influencing earnings management. The population of this study is a subsector company of other metals and mineral mines listed on the Indonesian stock exchange in the period 2016 – 2020. Samples that fit the researcher’s criteria as many as 40 and data are downloaded from www.idx.co.id. The analysis methods performed are descriptive, coefficient correlation, coefficient determination, simple regression, classical assumption test, normality test, multi correlation, significance test, multiple regression with significance level of 0.05 or 5%. The result of this study showed that leverage (X1) had a significant negative influence on earnings management with value of 0.844 > 0.05, and the audit committee (X2) with a proportion of the number of audit committee members of 0.002 < 0.05 had a significant positive influence on earnings management and the number of meetings of 0.215 > 0.05 had a negative significant on earnings management (Y), and f has a significant influence with a value of 0.011 < 0.05 simultaneously.